Adaptability Metric Analysis for Multi‐Mission Design of Manufactured Products and Systems. Issue 1 (13th September 2016) - Zhu, Haifeng; Murray, Brian; de Weck, Oliver; Skelding, Randy; Shougarian, Narek; Zeidner, Lawrence; Arnold, Eileen
Abstract: Adaptability in manufacturing is becoming increasingly important, as it provides flexibility without requiring significant up‐front investment. In this paper, we review the history of this concept, indicate issues with prior work and advance our knowledge of this topic. We provide an explanation and analysis on the concept of mission‐based adaptability that adopts a similar definition as the adaptability in ecosystems, which describes a system's adaptive capability relative to on‐going changes. Our analysis shows the mission‐based adaptability's empirical mathematical properties and indicates this formulation is able to resolve previous approaches' issues at an optimal level of abstraction. We employ extensive tools and analysis on an airplane engine design example case and demonstrate the importance and usefulness of the adaptability metric for decision makers in the manufacturing industry.2